PENAFSIRAN TELEOLOGIS/SOSIOLOGIS, PENAFSIRAN PURPOSIVE DAN AHARON BARAK: SUATU REFLEKSI KRITIS - M. Manullang, E. Fernando (Faculty of Law, Parahyangan Catholic University, 2019)
Teleological interpretation is construed the same as sociological interpretatio, because it cores on the intention and purpose in making a rule. Such interpretation is also known as purposive interpretation. However, unlike the teleological and purposive interpretations known in the continental and common law legal traditions, Aharon Barak proposed his version of purposive interpretation. This article seeks to explain as simple as possible what teleological interpretation, sociological interpretation, purposive interpretation within the common law tradition and purposive interpretation according to Aharon Barak.